Childhood nephrotic syndrome: genetic basis in studying and treatment - Liên, Nguyễn Thị Kim; Hoàng, Nguyễn Huy (Vietnam Journal of Biotechnology, 2016)
Childhood nephrotic syndrome is a serious disease with the high risk of mortality. The prevalence worldwide is approximately 2 to 7 cases per 100,000 children. Hitherto, the patients are treatmed with steroid or immunosuppressive therapy and renal transplantation. However, many patients are steroid resistant and have a high risk of recurrence. The mutations in seven genes (NHPS1, NPHS2, CD2AP, PLCE1, ACTN4, TRPC6, INF2) have been implicated in different forms of nephrotic syndrome. Among them, two genes, NPHS1 and NPHS2, encoding for nephrin and podocin protein of the glomerular filtration barrier, have a particularly serious influence in almost of cases and steroid resistance in patients. So that, in the world there were a lot of researches conducted to identify gene mutations that related to disease manifestations and the response to treatment in the patients who have different genetic background. Mutations in NPHS1 and NPHS2 are considered the main cause of 75% cases with nephrotic syndrome. And NPHS2 mutations related to 40% cases with steroid resistance in patients. These results will help the doctors to have an effective treatment for the patients. However, in Vietnam no study has yet been done to detect gene mutations in patients with nephrotic syndrome. In this article, we summarize the research which have been published to give an overview of the genetic basis of causing and treatment for childhood nephrotic syndrome.